William shakespeare's much ado about mean girls ebook - Doescher, Ian (Pop Shakespeare, 2019)
Celebrate Tina Fey's Mean Girls with this illustrated adaptation of the cult classic script, retold in Shakespearean verse by the best-selling author of William Shakespeare's Star Wars . On Wednesdays we array ourselves in pink! Mean Girls gets an Elizabethan makeover in this totally fetch comedy of manners about North Shore High’s queen bees, wannabes, misfits, and nerds. Written in the style of the Bard of Avon, William Shakespeare’s Much Ado About Mean Girls tells the story of Cady Heron’s rise from home-schooled jungle freak to one of the most popular girls in school. Every scene and line of dialogue from the iconic script is reimagined in authentic Shakespearean rhyme, meter and stage directions, complete with dramatic asides from Janis, Damian, Gretchen, and Karen. By the end, you’ll be surprised that Shakespeare didn’t pen this classic story of rivalries, betrayal, jealousy, obsession, and fastidious rule-making about when one can and cannot wear sweatpants.